Why osteoarthritis of the knee is called “a wound that does not heal” and why Tai Chi is an effective treatment - Huston, Patricia (Frontiers in Medicine, 2023)
Context Osteoarthritis (OA) of the knee is common and is associated with other chronic diseases and early mortality. OA is often described as a “wound that does not heal” because a local innate immune response gets dysregulated. Tai Chi is an aerobic mind-body practice that is recommended in national and international clinical practice guidelines as a treatment for OA of the knee. This review addressed two questions: What causes immune dysregulation in the knee? and Why is Tai Chi an effective treatment? Recent findings There is now a good understanding of what causes OA of the knee at the cellular level. OA begins in the synovium from a phenotypic shift in synovial macrophages in response to tissue damage. The synovial macrophages release inflammatory cytokines, as part of the first phase of the normal healing and repair process. Cytokines communicate to other cells that there has been damage. This stimulates chondrocytes, osteoblasts, and fibroblasts to release inflammatory cytokines as well. When tissue damage is repetitive, there is repetitive release of inflammatory cytokines, and the normal healing process stops. The most common cause of tissue damage is from abnormal biomechanical forces on the knee that arise from trauma, injury, and misalignment. Tissue damage is made worse when there is systemic low-grade inflammation associated with other chronic conditions. Pain and stiffness often result in decreased physical activity, which leads to muscle weakness, progressive instability of the joint, and an increased risk of falls, further injuring the knee. Tai Chi improves alignment, optimizes the biomechanical forces on the knee, strengthens the lower limbs, and decreases systemic inflammation. Tai Chi improves balance and decreases the risk of falls and further injury. There is clinical and experimental evidence to suggest that by removing the causes of cell dysregulation, Tai Chi enables the normal healing and repair process to resume. Conclusion Knee OA is a wound that does not heal primarily because repetitive adverse forces on the knee cause synovial macrophages and then local chondrocytes, osteocytes and fibroblasts to dysregulate and stop the normal healing and repair process. Tai Chi mitigates adverse forces on the knee and stabilizes the joint, creating the conditions whereby the normal healing and repair process can resume. Further research is needed.